Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1021/ol902004p
|View full text |Cite
|
Sign up to set email alerts
|

A Modular Rearrangement Approach toward Medicinally Relevant Phosphinic Structures

Abstract: An unprecedented coupling of a P-C and a C-C bond-forming event in a practical operation was developed to access medicinally relevant phosphinic structures. The strategy relies on an Ireland-Claisen rearrangement triggered by the phospha-Michael addition of silyl phosphonites to allyl acrylates. This protocol was extended to a more versatile three-component variant that utilizes phosphinic acids, acryloyl chlorides, and allylic alcohols as starting materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Other examples of cooperative effects were also reported [ 45 , 56 , 76 ]. One such example is cyclization of terminal groups.…”
Section: Modifications Following the C-p-c Formationmentioning
confidence: 76%
See 1 more Smart Citation
“…Other examples of cooperative effects were also reported [ 45 , 56 , 76 ]. One such example is cyclization of terminal groups.…”
Section: Modifications Following the C-p-c Formationmentioning
confidence: 76%
“…An interesting possibility of tandem P-C and C-C bond formation on a phosphinic dipeptide scaffold was recognized in a preliminary way in the Yiotakis group [ 56 ]. The tandem bond formation involved phospha-Michael addition of a P-H substrate to allyl acrylate ( 25 ) followed by a Claisen-type rearrangement ( Scheme 6 ).…”
Section: Synthesis Of the Phosphinic αα'-Dipeptide Backbonementioning
confidence: 99%
“…For this purpose, MBHA 6 m was synthesized, as shown in Scheme . The choice of cinnamyl ester was based on our previous work in which an increased propensity for rearrangement in cinnamyl acrylic esters was observed 6a. In the same study, significantly increased rates of rearrangement were also observed in the case of α‐substituted acrylates, a condition that is met in 6 m .…”
Section: Resultsmentioning
confidence: 97%
“…Compound 98 was further transformed into the target pseudopeptide 99 in 2% overall yield through a six steps sequence, whose biological activity lied below the sensitivity of the enzyme assay used (<1 nM) (Scheme 41). Additionally, Yiotakis et al [87] developed an Ireland-Claisen rearrangement triggered by the phospha-Michael addition of silyl phosphonites to allyl acrylates, as a new strategy to access pharmacologically relevant C-phosphinic derivatives. In this context, the reaction of Cbz-protected phenylalanine H-phosphinic analogue (R)-66a [72] with the acrylate in the presence of DIPEA in CH2Cl2 followed by addition of TMSCl at −78 °C, provided the P-alkylated α-amino-C-phosphinic acid (R)-100 in 52% yield with retention of configuration at phosphorus atom (Scheme 42).…”
Section: Scheme 32 Synthesis Of the C-phosphinic Acid 75 And Its Actmentioning
confidence: 99%
“…In this context, the reaction of Cbz-protected phenylalanine H-phosphinic analogue (R)-66a [72] with the acrylate in the presence of DIPEA in CH2Cl2 followed by addition of TMSCl at −78 °C, provided the P-alkylated α-amino-C-phosphinic acid (R)-100 in 52% yield with retention of configuration at phosphorus atom (Scheme 42). Additionally, Yiotakis et al [87] developed an Ireland-Claisen rearrangement triggered by the phospha-Michael addition of silyl phosphonites to allyl acrylates, as a new strategy to access pharmacologically relevant C-phosphinic derivatives. In this context, the reaction of Cbz-protected phenylalanine H-phosphinic analogue (R)-66a [72] with the acrylate in the presence of DIPEA in CH 2 Cl 2 followed by addition of TMSCl at −78 • C, provided the P-alkylated α-amino-C-phosphinic acid (R)-100 in 52% yield with retention of configuration at phosphorus atom (Scheme 42).…”
Section: Scheme 32 Synthesis Of the C-phosphinic Acid 75 And Its Actmentioning
confidence: 99%